The Bible and its translations: colonial and postcolonial encounters with the indigenous - Jacobus A. Naudé (Acta Theologica)
From text: The translation of the Bible is the one publishing success story in the third world. It seemed to have overcome the natural resistance of a primary oral culture to the written word. In the past the Bible and its translations into the indigenous languages of the colonised represented colonial empowerment. In recent years, however, the status quo seems to have changed. By means of a process of indigenisation of the translated versions of the Bible, these translations have come to prescribe and dominate biblical dialogue, the nature of the colonial encounter between the source text and translations, and the target audiences, by commenting on the cultural mechanisms of ownership, resistance and indigenisation as vacillating media of oppression and liberation.